Synthesis ,Characterization and Study Biological Activity of Some New 1, 3, 4-Thiadiazole and Pyrazolone Derivatives Containing Indole Ring - Khalid F. Ali; Kadhim M. Lazim; Jumbad H. Tomma (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
This work involves synthesis and characterization of some new 1, 3, 4-thiadiazole or pyrazoline derivatives  heterocyclic containing indole ring. The new 2-amino-1, 3, 4thiadiazole derivatives[IV] and [V]a, b were synthesized by cyclization reaction of 2-methyl1H-indole-carbothiosemicarbazide[III] in H2SO4 acid or by reaction of indole-3-acetic acid or indole-3-butanoic acid with thiosemicarbazide in the presence of phosphorous oxychloride, respectively. Amide derivatives [VI]-[VIII] were synthesized by the reaction equimolar of 2amino-1, 3, 4-thiadiazoles and (acetyl chloride, benzoyl chloride, anisoyl chloride and heptanoyl chloride) in DMF and pyridine as accepter. The new pyrazolone  derivatives [XI]a, b were synthesized from heating under reflux equimolar from a mixture of acid  hydrazides [X]a or [X]b  and  ethylacetoacetate  in absolute ethanol. Acetyl pyrazolone compounds[XII]a, b were synthesized by the reaction of pyrazolone  derivatives [X]a or [X]b with acetyl chloride in 1,4-Dioxane in present of calcium hydroxide to give 4-acetyl pyrazolone derivatives[XI]a, b. The new aryl hydrazone derivatives of  pyrazoline [XIII]  and [XIV] were synthesized  by the  reaction of one mole of compounds [XII]a or [XII]b with one mole of  phenyl hydrazine or  substituted phenyl hydrazine in ethanol. All the synthesized compounds have been characterized by melting points , FTIR, 1HNMR and Mass spectroscopy (of some of theme).